Hydraulic fracturing in cave mining: Opportunities for improvement - Rimmelin, R; Chitombo, G; Rojas, E (MassMin 2020: Proceedings of the Eighth International Conference & Exhibition on Mass Mining, 2020)
Hydraulic Fracturing (HF) in cave mining is commonly used in competent rock under high stresses and seismic conditions, to manage risks associated with induced seismicity and cave propagation. The HF process is done using up holes drilled from the undercut level (e.g. El Teniente - Codelco) or down holes from an upper level (e.g. Newcrest mining). Discrete fractures assumed to be in the order of 20 to 40 m in diameter are then created every 1.5 m or 2.5 m along the drill holes, using water at higher pressures. In comparison, other industry experience such as Petroleum, HF is based on similar principles in terms of the drill hole alignment with the principal stresses and the use of water at high pressures, but more efficient during the process of the creation of the network of fractures. The network of fractures thus created covers a volume rather than discrete fractures and could be as long as 100 m. Currently, petroleum HF process is carried out from the surface down to 3,000 m in depth. Also, the use of additional materials such as “sand” to improve the propagation of fractures is another example of Petroleum practices that can be used in Cave Mining. Another point of discussion relies on the current practices in Cave mining, in which, stress anisotropy is not considered to address important topics such as efficiency of the HF process and spatial distribution of the HF holes, for a better coverage of the rock mass. Hydraulic Fracturing is increasingly becoming an essential enabling tool in deep hard rock cave mining, and some of the current HF practices used in the Petroleum industry offer an opportunity to improve the cave mining HF processes. This paper proposes the use of known rock mechanics principles for the cave mining industry to adopt practices used in the Petroleum to achieve the intended outcomes from HF as currently used in cave mining.